Penerapan Higiene Sanitasi dan Keselamatan Kerja Pengolah Makanan pada Unit Gizi di RS X Tahun 2024: Implementation of Hygiene, Sanitation, and Occupational Safety Practices among Food Handlers in the Nutrition Unit at Hospital X - Gunaputri, Ramandha Eka; Rindu, Rindu; Syafei, Abdullah (MPI Press, 2025)
Introduction: In Indonesia, it is estimated that more than 20 million cases of food poisoning occur each year, with a considerable portion linked to hospital kitchens. This alarming statistic underscores the critical need for strict adherence to hygiene and sanitation standards, as well as occupational safety protocols in food processing. Despite the presence of regulations, including the Indonesian Ministry of Health's guidelines on food hygiene and sanitation, challenges persist. Method: This study employed a qualitative case study approach to provide an in-depth exploration of the phenomena associated with hygiene, sanitation, and occupational safety practices, emphasizing the perspectives and experiences of those involved. Result: Food handlers demonstrated adequate knowledge; however, implementation of hygiene, sanitation, and occupational safety was inconsistent, particularly in PPE use and SOP adherence. Long working hours and kitchen conditions affected compliance. Food receiving procedures complied with Minister of Health Regulation No. 2 of 2023. Conclution: The study concludes that although employees in RS X's nutrition department are aware of hygiene, sanitation, and occupational safety, there are notable gaps in their implementation. This includes inconsistent use of personal protective equipment (PPE), incomplete adherence to standard operating procedures, and insufficient training on workplace safety.